Protein S testing in patients with protein S deficiency, factor V Leiden, and rivaroxaban by North American Specialized Coagulation Laboratories - Smock, Kristi J.; Plumhoff, Elizabeth A.; Meijer, Piet; Hsu, Peihong; Zantek, Nicole D.; Heikal, Nahla M.; Van Cott, Elizabeth M. (Thrombosis and Haemostasis, 2016)
In 2010–2012, the North American Specialized Coagulation Laboratory Association (NASCOLA) distributed 12 proficiency testing challenges to evaluate laboratory testing for protein S (PS). Results were analysed to assess the performance of PS activity, PS free antigen, and PS total antigen testing. Statistical analysis was performed on the numeric results and qualitative classification submitted for each method. There were 2,106 total results: 716 results from PS activity assays, 833 results from PS free antigen assays, and 557 results from PS total antigen assays. The three assay types performed well in the classification of five normal samples and nine abnormal samples, although certain PS activity methods were more likely to classify normal samples as abnormal and one PS total antigen assay was more likely to classify abnormal samples as normal. PS activity methods were affected by interfering substances such as heterozygous or homozygous factor V Leiden mutation (underestimation) and the anticoagulant drug rivaroxaban (overestimation). In conclusion, NASCOLA laboratories using a variety of PS assays performed well in the classification of clearly normal and abnormal samples. Laboratories performing PS activity assays should be aware of potential interferences in samples positive for FV Leiden or containing certain anticoagulant medications.
Keywords: Protein S; proficiency testing; NASCOLA; factor V Leiden; direct oral anticoagulants